Local Exhaust Ventilation: PAST, PRESENT, and FUTURE - Hasan, Nor Halim; Said, M. R; Leman, A. M (2012)
Engineering control is a method of controlling the risk of exposure to contaminants. Health effects to industrial workers are more severe whilst high exposure and time exposed to contaminants at workplace. Installation of industrial ventilation or local exhaust ventilation (LEV) system is the proposed method to reduce the risk. This paper discusses the past, present and future relating to LEV system in Malaysia. Current issues related to monitoring reported by Hygiene Technician in compliance with Occupational Safety and Health (Use of Standard Chemical Hazardous to Health Regulation 2000) carried out in several states in Malaysia as a sample. The nanotechnology is a new area at present and future. The involvement of government, employers and employees need to be justified due to the attention to prevent and control of any exposure. It is suggested that using the Computational Fluid Dynamic (CFD) simulation, a new design of LEV system can be upgraded and predicted.